Living on the edge: how does environmental risk affect the behavioural and cognitive ecology of prey?. (May 2016) - Mitchell, Matthew D.; Chivers, Douglas P.; Brown, Grant E.; Ferrari, Maud C.O.
Abstract : Prey show remarkable plasticity across a range of traits that allow them to adapt to changes in predation risk in their local environment. While we know much about behavioural, morphological, physiological and life-history responses, we know less about how background risk alters cognitive functioning related to risk assessment. Here, we exposed wood frog tadpoles, Lithobates sylvaticus, to high- or low-risk environments for 7 days. Following this, we exposed tadpoles to one of four treatments that either continued risk, ended risk, taught tadpoles to recognize a predator or provided a false predator learning control. Tadpoles were tested for responses to predator odour, alarm cues or water either 1 day or 11 days after conditioning ended. Comparisons between conditioning treatments and test odours allowed us to assess how background risk alters a range of cognitive functions relating to risk assessment. Tadpoles that experienced high background risk responded to alarm cues with a weaker response than low-risk tadpoles, as predicted by the risk allocation hypothesis. High-risk tadpoles also developed neophobic responses to novel odours, unlike low-risk tadpoles, but displayed similar responses to a learned predator as tadpoles from low risk. When tested again 11 days later, high- and low-risk tadpoles responded equally across all treatments with the exception of learned predator responses, where high-risk tadpoles still responded strongly to the predator odour, while low-risk tadpoles did not. Our results demonstrate that recent experience with risk induces short-term cognitive plasticity in a number of functions related to risk assessment. Highlights: We investigated how experience alters cognitive traits related to risk assessment in tadpoles. High background risk induced neophobia in tadpoles. High-risk tadpoles showed a weaker response to risk than low-risk tadpoles. Background risk altered memory but not response intensity when learning predators. Tadpoles showed short-term cognitive plasticity in risk assessment.